ANATOMI, KOMPONEN BIOAKTIF DAN AKTIVITAS ANTIOKSIDAN DAUN MANGROVE API-API (Avicennia Marina) - Agoes Mardiono Jacoeb; Sri Purwaningsih; Rinto . (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
The study about chemical and physical characteristics, bioactive compounds and antioxidant activity of mangrove api-api (Avicennia marina) leaf have been done. The structure of leaf tissues was analyzed with microscopic method, chemical compositions were determined by proximate analysis, antioxidant activity was determined by DPPH method, while bioactive compounds were determined by phytochemical assay. The microscopic analysis shown that api-api’s leaf have common feature dicotyl leaves structure, but it has a unique additional structure, that was salt extruding gland. The result of proximate analysis showed that api-api’s leaf was high in crude fiber (4.12%) and carbohydrate (23.00%). Ethyl acetate extract of api-api’s leaf showed higher antioxidant activity than hexane and methanol extracts, with IC value is 182.33 ppm. The ethyl acetate extract in concentration 300 ppm had higher ability to inhibite autooxidation that occurred in oil/water emulsion. Flavonoid, steroid dan reduction sugar were detected in api-api leaf extract.Keywords: antioxidant activity, Avicennia marina, DPPH, flavonoid, salt extruding gland.